P1-S2.43 Behavioural and biological surveillance among man who have sex with man using respondent-driven sampling methodology in Manaus, Amazon, Brazil. (10th July 2011) - Benzaken, A S; Galban, E G; Benzaken, N S; , C K; Pinho, A; Mello, M; Vasquez, F; Barros, C A; Sansigolo Kerr, L R Franco
Abstract : Background: There is a renewed interest in including men who have sex with men (MSM) in global HIV surveillance. A multicenter study of 10 Brazilian cities was designed to generate a national-level estimate the prevalence of HIV and syphilis among MSM. This abstracts presents the results of one of the participating cities. Objectives: To establish a baseline among MSM in Manaus to continuously monitor the prevalence of HIV and syphilis infection, level of knowledge about STI/HIV/AIDS, prevailing sexual attitudes and practices, and frequency of acts of discrimination against MSM. Methodology: A cross-sectional study of 824 MSM (>18 years old) was conducted from October to May 2008 using respondent-driven sampling (RDS)- a chain-link and snowball sampling method that generates probability-based samples and is systematic, so it can be used to develop comparable surveillance data. Results: The weighted prevalence obtained with the use of Respondent-Driven Sampling Analysis Tool (RDSAT) software were 6.8% (CI 4.9 to 9.8) for HIV and 4.0% (CI 2.6 to 5.8) for syphilis. A number of participants reported sex with both men and women (47.8% of HIV positive and 56.1% of syphilis cases), while 20% of HIV positive and 30% of syphilis cases classified themselves as gay or homosexual. A previous infection of syphilis was the main predictive variables associated with HIV. The average age of first intercourse was 13.25 (with a range 5−23). This pattern of early sex suggests abuse. Fifty four point five per cent of participants had their first sexual intercourse with men, 42.6% with women, and 2.2% with transvestites. Participants also reported—41% (CI 37 to 47) used condoms in their first relationship, 73.1% (CI 69.7 to 77.2) had at least one casual sex partner during the previous 12 months, 31.6% (CI 27.7 to 35.9) used condoms consistently with casual relationships if they were with men and 15.5% (CI 11.9 to 18.9) with a woman. Nineteen per cent of MSM said they had been the target of direct physical aggression due to their sexual identity, 10% reported being forced to have sex against their will, and over 30% reported being humiliated or disrespected because of their sexual orientation. Conclusions: The prevalence of HIV and syphilis infection in MSM in the city of Manaus is relatively high. There is substantial discrimination against MSM. The need of specific public policy and awareness campaigns for this vulnerable group is urgent.